A kind of anti-corrosion kerbstone and preparation method thereof
Through the use of specific formulas and preparation processes in the roadside stone, the problem of traditional road along the stone along the stones facing car tail gas pollution, salt erosion, and insufficient permeability, significantly improved the pressure resistance and corrosion of the road along the road along the road along the road along the road along the stone along the stone along the road along the stone along the road edge stone. Performance extends the service life and reduces environmental pollution.
Patent Information
- Application Number
- CN202211321003.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-10-26
AI Technical Summary
Traditional curbs have short service life and great environmental damage when facing the problems of automobile exhaust pollution, salt corrosion and insufficient permeability.
A formula of anti-corrosion curb stone is adopted, including cement, inorganic slag powder, water reducing agent, admixture, anti-aging agent, bicarbonate, curing agent, fine aggregate, bentonite and nano-oxide. The ratio and preparation process improve the compressive strength, erosion resistance and frost resistance of the curb stone.
Significantly improves the compressive strength and anti-erosion properties of curb stones, prolongs service life, and reduces environmental pollution.
Smart Images

Figure BDA0003910424390000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of road engineering, and its classification number is C04B28 / 04. Specifically, it relates to a corrosion-resistant curbstone and a preparation method thereof. Background Art
[0002] Traditional curbstones are generally made from natural rocks, but mining rocks involves blasting rocks, which seriously damages the natural environment. In addition, the process of processing rocks requires cutting and grinding, which produces a large amount of wastewater and dust, further polluting the environment. Of course, curbstones are now made from concrete, but curbstones made from concrete still have the following problems: (1) Car exhaust pollutes the curbstones, shortening their service life. (2) In winter, in order to melt the snow on the road, some snow-melting salt (mainly sodium chloride) is usually sprinkled, which can easily cause the curbstones to be damaged by salt corrosion. (3) The curbstones have poor impermeability, shortening their service life.
[0003] Patent CN112745054 discloses a salt-resistant marine concrete admixture and a preparation method thereof. The addition of modified fibers can greatly improve the strength of concrete. High-permeability nanomaterials can effectively prevent the invasion of harmful substances such as chloride ions, thereby improving the concrete's impermeability, resistance to sulfate erosion and chloride ion erosion. However, it does not solve the hazards caused by automobile exhaust pollution.
[0004] Patent CN103397585 discloses a method for preparing a concrete component that can absorb and degrade automobile exhaust. The method utilizes titanium dioxide to degrade automobile exhaust. Although the problem of degrading automobile exhaust can be solved, the salt corrosion and frost resistance of concrete are not solved. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present invention provides a corrosion-resistant curbstone, whose raw materials include, by weight: 20-40 parts of cement, 2-10 parts of inorganic slag powder, 0.1-2 parts of water reducer, 1-10 parts of admixture, 1-5 parts of anti-aging agent, 1-5 parts of bicarbonate, 2-10 parts of curing agent, 5-15 parts of fine aggregate, 5-20 parts of bentonite, 0.5-3 parts of nano oxide, and the balance is water.
[0006] Further preferably, the raw materials of the corrosion-resistant curbstone include, by weight: 30-40 parts of cement, 4-8 parts of inorganic slag powder, 0.3-1 parts of water reducer, 5-10 parts of admixture, 1-3 parts of antioxidant, 3-5 parts of bicarbonate, 2-4 parts of curing agent, 5-10 parts of fine aggregate, 10-15 parts of bentonite, 1-3 parts of nano oxide, and the balance is water.
[0007] Further preferably, the raw materials of the corrosion-resistant curbstone include, by weight: 35 parts of cement, 6 parts of inorganic slag powder, 0.6 parts of water reducer, 8 parts of admixture, 2 parts of antioxidant, 4 parts of bicarbonate, 2.3 parts of curing agent, 8 parts of fine aggregate, 13 parts of bentonite, 2 parts of nano oxide, and the balance is water.
[0008] Further preferably, the cement is silicate cement, the inorganic slag powder is steel slag powder, the anti-aging agent is UV-531, and the bicarbonate is calcium bicarbonate.
[0009] Preferably, the mass ratio between the cement and the fine aggregate is (30-40):(5-10).
[0010] Further preferably, the mass ratio between the cement and the fine aggregate is 35:8.
[0011] Preferably, the water reducer includes at least one of an organosilicon water reducer, a polycarboxylic acid water reducer, a naphthalene-based high-efficiency water reducer, and a sulfonate water reducer.
[0012] More preferably, the water reducer is a polycarboxylate water reducer.
[0013] Preferably, the admixture is hydroxyethylidene diphosphonic acid.
[0014] Preferably, the mass ratio between the water reducer and the admixture is (0.3-1): (5-10). The polycarboxylate water reducer can reduce the pores in the formed cement mortar and reduce the erosion of the curbstone by moist air through the pores after the concrete forms a solid. Hydroxyethylated diphosphonic acid can form a complex with calcium ions in the concrete, and can well control the concentration of calcium ions in the liquid phase at the initial stage of hydration, achieving a slow setting effect, and can enhance the later strength of the concrete. The applicant unexpectedly found that when the mass ratio of the polycarboxylate water reducer and the admixture hydroxyethylated diphosphonic acid is (0.3-1): (5-10), the porosity of the concrete is improved, and the anti-erosion and compressive strength of the product curbstone are improved. At the same time, under the action of the polycarboxylate water reducer, the fluidity between cement and fine aggregate is improved, so that cement and fine aggregate can be fully combined, and the compressive strength and anti-erosion performance are further enhanced.
[0015] Further preferably, the mass ratio between the water reducing agent and the admixture is 0.6:8.
[0016] Preferably, the curing agent includes at least one of calcium chloride, sodium citrate, sodium carbonate and citric acid.
[0017] Further preferably, the curing agent is a mixture of calcium chloride, sodium citrate and sodium carbonate. The applicant has found that the addition of sodium citrate, sodium carbonate and calcium chloride can improve the anti-seepage and water-blocking ability of the curbstone. Sodium citrate, sodium carbonate and calcium chloride can react with free oxides such as calcium and aluminum in concrete, and the generated crystals can make the concrete firmly bonded, which plays a role in enhancing the waterproofing of the curbstone. Among them, sodium carbonate absorbs water and expands in the pores of the concrete, which reduces the porosity of the concrete and increases the density. Under the synergistic effect of the water reducer, aggregate and nano-titanium dioxide, the anti-seepage and water-blocking ability of the curbstone is improved.
[0018] Further preferably, the mass ratio of calcium chloride, sodium citrate and sodium carbonate is (1-3):(0.05-0.2):(0.1-0.3).
[0019] Further preferably, the mass ratio of calcium chloride, sodium citrate and sodium carbonate is 2:0.1:0.2.
[0020] Preferably, the fine aggregate includes at least one of fly ash, metakaolin, earth and stone powder, gravel and river sand.
[0021] Further preferably, the fine aggregate is a mixture of fly ash, metakaolin, earth and stone powder, and river sand.
[0022] Further preferably, the mass ratio of the fly ash, metakaolin, earth and stone powder and river sand is 3:3:1:1.
[0023] Preferably, the bentonite is at least one of organic bentonite, calcium-based bentonite, sodium-based bentonite, and organic-inorganic composite modified bentonite.
[0024] Further preferably, the bentonite is organic bentonite.
[0025] Preferably, the nano-oxide is nano-titanium dioxide and / or nano-silicon dioxide.
[0026] Further preferably, the nano-oxide is nano-titanium dioxide with an average particle size of 30 nm.
[0027] The applicant has found that the addition of nano titanium dioxide can degrade nitrogen oxides in automobile exhaust. Nano titanium dioxide has a photocatalytic effect and can promote the decomposition of exhaust gases such as nitrogen dioxide and carbon monoxide emitted by vehicles. At the same time, nano carbon dioxide can fill the pores on the interface between aggregate and cement in concrete, effectively preventing the invasion of harmful substances such as chloride ions. Under the joint action of fine aggregate metakaolin and fly ash, the density of concrete is improved, the erosion of salt solution is reduced, and the salt corrosion resistance and frost resistance of curbstone are improved.
[0028] The second aspect of the present invention provides a method for preparing a corrosion-resistant kerbstone, comprising the following steps:
[0029] (1) Preparation of concrete;
[0030] Under the condition of a stirring speed of 500-800rpm / min, nano oxide, water and water reducing agent are added into the mixer according to weight parts. After 5-10 minutes, a nano particle solution is prepared. At the same stirring speed, cement, inorganic slag powder, admixture, curing agent, fine aggregate and bentonite are added in order according to weight parts and stirred for 10-40 minutes to prepare concrete.
[0031] (2) Preparation of kerbstones.
[0032] Add concrete to the molding machine for vibration molding, the exciting force is 100-300KN, the frequency is 50-70HZ, and the time is 20-120s. After molding, it is transported to the curing room. The curing is divided into three stages. The first stage is a constant temperature curing temperature of 40-50℃, the time is 3-4h, the second stage is a constant temperature curing temperature of 55-65℃, the curing time is 2-4h, and the third stage is a constant temperature curing temperature of 40-45℃, the curing time is 2-3h, and the product of corrosion-resistant curbstone is obtained.
[0033] Beneficial effects: (1) In the present invention, nano-titanium dioxide promotes the decomposition of waste gases such as nitrogen dioxide and carbon monoxide emitted by vehicles. At the same time, the cooperation between nano-titanium dioxide and fine aggregate improves the salt corrosion resistance and frost resistance of the curbstone.
[0034] (2) When the mass ratio of the polycarboxylate water-reducing agent to the admixture hydroxyethylidene diphosphonic acid is (0.3-1):(5-10) in the present invention, the compressive strength and erosion resistance of the curbstone are improved.
[0035] (3) The curing agent used in the present invention is a mixture of calcium chloride, sodium citrate and sodium carbonate, which makes the concrete firmly bonded, reduces the porosity and increases the density. Under the synergistic effect of the water reducer, aggregate and nano-titanium dioxide, the anti-seepage and water-blocking ability of the curbstone is improved, and the service life of the curbstone is extended. Example
[0036] Example 1
[0037] A corrosion-resistant curbstone comprises, by weight, 35 parts of cement, 6 parts of inorganic slag powder, 0.6 parts of water reducing agent, 8 parts of admixture, 2 parts of anti-aging agent, 4 parts of bicarbonate, 2.3 parts of curing agent, 8 parts of fine aggregate, 13 parts of bentonite, 2 parts of nano oxide, and the balance is water.
[0038] The cement is silicate cement, and the mass ratio of the silicate cement to fine aggregate is 35:8.
[0039] The inorganic slag powder is steel slag powder.
[0040] The water reducer is a polycarboxylate water reducer purchased from Guangzhou Zhongye Chemical Co., Ltd., model TEPG.
[0041] The admixture is hydroxyethylidene diphosphonic acid, and its CAS number is 2809-21-4.
[0042] The mass ratio between the water reducing agent and the admixture is 0.6:8.
[0043] The anti-aging agent is UV-531.
[0044] The bicarbonate is calcium bicarbonate.
[0045] The curing agent is a mixture of calcium chloride, sodium citrate and sodium carbonate, and the mass ratio of the three is 2:0.1:0.2.
[0046] The fine aggregate is a mixture of fly ash, metakaolin, earth and stone powder, and river sand, and the mass ratio of the four is 3:3:1:1.
[0047] The bentonite is organic bentonite.
[0048] The nano oxide is nano titanium dioxide, and the average particle size is 30nm.
[0049] A method for preparing a corrosion-resistant kerbstone, comprising the following steps:
[0050] (1) Preparation of concrete;
[0051] Under the condition of a stirring speed of 600 rpm / min, nano oxide, water and water reducing agent are added into the mixer according to weight parts. After 8 minutes, a nano particle solution is prepared. Under the same stirring speed, cement, inorganic slag powder, admixture, curing agent, fine aggregate and bentonite are added in sequence according to weight parts and stirred for 30 minutes to prepare concrete.
[0052] (2) Preparation of kerbstones.
[0053] Add concrete into the molding machine for vibration molding, the exciting force is 300KN, the frequency is 60HZ, and the time is 80s. After molding, it is transported to the curing room. The curing is divided into three stages. The first stage is a constant temperature curing temperature of 45℃, the time is 4h, the second stage is a constant temperature curing temperature of 60℃, the curing time is 3h, and the third stage is a constant temperature curing temperature of 45℃, the curing time is 3h, and the product of corrosion-resistant curbstone is obtained.
[0054] Example 2
[0055] A corrosion-resistant curbstone comprises, by weight, 35 parts of cement, 6 parts of inorganic slag powder, 0.3 parts of water reducing agent, 5 parts of admixture, 2 parts of anti-aging agent, 4 parts of bicarbonate, 3.5 parts of curing agent, 8 parts of fine aggregate, 13 parts of bentonite, 2 parts of nano oxide, and the balance is water.
[0056] The cement is silicate cement, and the mass ratio of the silicate cement to fine aggregate is 35:8.
[0057] The inorganic slag powder is steel slag powder.
[0058] The water reducer is a polycarboxylate water reducer purchased from Guangzhou Zhongye Chemical Co., Ltd., model TEPG.
[0059] The admixture is hydroxyethylidene diphosphonic acid, and its CAS number is 2809-21-4.
[0060] The mass ratio between the water reducing agent and the admixture is 0.3:5.
[0061] The anti-aging agent is UV-531.
[0062] The bicarbonate is calcium bicarbonate.
[0063] The curing agent is a mixture of calcium chloride, sodium citrate and sodium carbonate, and the mass ratio of the three is 3:0.05:0.3.
[0064] The fine aggregate is a mixture of fly ash, metakaolin, earth and stone powder, and river sand, and the mass ratio of the four is 3:3:1:1.
[0065] The bentonite is organic bentonite.
[0066] The nano oxide is nano titanium dioxide, and the average particle size is 30nm.
[0067] A method for preparing a corrosion-resistant kerbstone, comprising the following steps:
[0068] (1) Preparation of concrete;
[0069] Under the condition of a stirring speed of 600 rpm / min, nano oxide, water, and water reducing agent were added into the mixer according to weight parts. After 8 min, a nano particle solution was prepared. At the same stirring speed, cement, inorganic slag powder, admixture, curing agent, fine aggregate, and bentonite were added in sequence according to weight parts and stirred for 30 min to prepare concrete.
[0070] (2) Preparation of kerbstones.
[0071] The concrete is added to the molding machine for vibration molding, with an exciting force of 300KN, a frequency of 60HZ, and a time of 80s. After molding, it is transported to the curing room. The curing is divided into three stages. The first stage is a constant temperature curing temperature of 45℃.
[0072] The time is 4h, the second stage constant temperature curing temperature is 60℃, the curing time is 3h, the third stage constant temperature curing temperature is 45℃, the curing time is 3h, and the product corrosion-resistant curbstone is obtained.
[0073] Example 3
[0074] A corrosion-resistant curbstone comprises, by weight, 35 parts of cement, 6 parts of inorganic slag powder, 0.6 parts of water reducing agent, 8 parts of admixture, 2 parts of anti-aging agent, 4 parts of bicarbonate, 2.3 parts of curing agent, 8 parts of fine aggregate, 13 parts of bentonite, 3 parts of nano oxide, and the balance is water.
[0075] The cement is silicate cement, and the mass ratio of the silicate cement to fine aggregate is 35:8.
[0076] The inorganic slag powder is steel slag powder.
[0077] The water reducer is a polycarboxylate water reducer purchased from Guangzhou Zhongye Chemical Co., Ltd., model TEPG.
[0078] The admixture is hydroxyethylidene diphosphonic acid, and its CAS number is 2809-21-4.
[0079] The mass ratio between the water reducing agent and the admixture is 0.6:8.
[0080] The anti-aging agent is UV-531.
[0081] The bicarbonate is calcium bicarbonate.
[0082] The curing agent is a mixture of calcium chloride, sodium citrate and sodium carbonate, and the mass ratio of the three is 2:0.1:0.2.
[0083] The fine aggregate is a mixture of fly ash, metakaolin, earth and stone powder, and river sand, and the mass ratio of the four is 4:2:1:1.
[0084] The bentonite is organic bentonite.
[0085] The nano oxide is nano titanium dioxide, and the average particle size is 30nm.
[0086] A method for preparing a corrosion-resistant kerbstone, comprising the following steps:
[0087] (1) Preparation of concrete;
[0088] Under the condition of a stirring speed of 600 rpm / min, nano oxide, water, and water reducing agent were added into the mixer according to weight parts. After 8 min, a nano particle solution was prepared. At the same stirring speed, cement, inorganic slag powder, admixture, curing agent, fine aggregate, and bentonite were added in sequence according to weight parts and stirred for 30 min to prepare concrete.
[0089] (2) Preparation of kerbstones.
[0090] Add concrete into the molding machine for vibration molding, the exciting force is 300KN, the frequency is 60HZ, and the time is 80s. After molding, it is transported to the curing room. The curing is divided into three stages. The first stage is a constant temperature curing temperature of 45℃, the time is 4h, the second stage is a constant temperature curing temperature of 60℃, the curing time is 3h, and the third stage is a constant temperature curing temperature of 45℃, the curing time is 3h, and the product of corrosion-resistant curbstone is obtained.
[0091] Comparative Example 1
[0092] No curing agent sodium carbonate was added, and the mass ratio of calcium chloride to sodium citrate was changed to 2:0.3. The rest was the same as in Example 1.
[0093] Comparative Example 2
[0094] Without adding titanium dioxide, the fine aggregate is a mixture of fly ash, metakaolin, earth and stone powder, and river sand, and the mass ratio of the four is changed to 5:1:1:1. The rest is the same as in Example 1.
[0095] Comparative Example 3
[0096] The mass ratio of the water reducing agent polycarboxylate water reducing agent to the admixture hydroxyethylidene diphosphonic acid was changed to 3:7, and the mass ratio of cement to fine aggregate was changed to 50:10. The rest was the same as in Example 1.
[0097] Performance Evaluation
[0098] (1) Water absorption test: Examples 1-3 and Comparative Examples 1-3 were tested according to the test standard JC / T 899-2016. The test results are shown in Table 1 below.
[0099] (2) Salt-freeze resistance test: Examples 1-3 and Comparative Examples 1-3 were tested according to the test standard GB / T50082-2009. The initial compressive strength and the compressive strength after 28 salt-freeze cycles were tested using a DYE-2000D electro-hydraulic concrete pressure testing machine, and the pressure loading rate was 0.5 to 0.8 MPa / s.
[0100] Table 1
[0101]
Claims
1. A corrosion-resistant kerbstone, characterized in that: The raw materials include, by weight: 20-40 parts of cement, 2-10 parts of inorganic slag powder, 0.1-2 parts of water reducing agent, 1-10 parts of admixture, 1-5 parts of anti-aging agent, 1-5 parts of bicarbonate, 2-10 parts of curing agent, 5-15 parts of fine aggregate, 5-20 parts of bentonite, 0.5-3 parts of nano oxide, and the balance is water; The mass ratio between the cement and the fine aggregate is (30-40):(5-10); The fine aggregate is a mixture of fly ash, metakaolin, earth and stone powder, and river sand, and the mass ratio of the fly ash, metakaolin, earth and stone powder and river sand is 3:3:1:1; The admixture is hydroxyethylidene diphosphonic acid; the water reducer is polycarboxylic acid water reducer; the mass ratio between the water reducer and the admixture is (0.3-1): (5-10); The curing agent is a mixture of calcium chloride, sodium citrate and sodium carbonate; the mass ratio of the calcium chloride, sodium citrate and sodium carbonate is (1-3): (0.05-0.2): (0.1-0.3); The nano oxide is nano titanium dioxide with an average particle size of 30 nm; The bentonite is organic bentonite.
2. A method for preparing the corrosion-resistant kerbstone according to claim 1, characterized in that: Here are the steps: (1) Preparation of concrete; (2) Preparation of kerbstones.
Citation Information
Patent Citations
Anti-freezing concrete water reducer
CN106116232A
Method for preparing concrete waterproof material
CN108975811A
Assembled road edge stone integrated pouring concrete road and construction method
CN114059415A